Globalization and Foreign Direct Investments - Elena Chirila-Donciu (CES Working Papers, 2013)
Mobilizing financial resources to cover investment needs is a concern of all countries, developed or developing ones, of consolidated market economies or emerging ones. A distinctive characteristic of Global Economy over the last few decades has been the rising rate and impressive increase in Foreign Direct Investment (FDI). The purpose of this research is to analyse global FDI inflows in Europe and in Romania. The results of the research support the idea that the balance of economic power is changing in the world economy and the countries that own a stable and solid industrial base are at an advantage. The new trends determined by the economic crisis in the field of FDI refer to the growing percentage of developing and emerging countries in the global flows of FDI.
Keywords: E22; F44; P33; 330; cforeign direct investments; globalization Romania